The PITCH study: Pitcher injuries during the first thirty days of the COVID-19-halted MLB season - Bonner, K. H.; Haberl, J. K.; Kirshblum, S. C.; Ashraf, H. (JSES Reviews, Reports, and Techniques, 2021)
Background: Major League Baseball (MLB) was among the first professional team sports to resume play in the United States after public health measures related to the appearance of Coronavirus Disease 2019 (COVID-19) caused interruptions to preseason training and major alterations to regular season play. There was a high level of concern that these athletes were ill-prepared for competition and would experience an increased risk of injury under the restricted play rules. Methods: The data in our study was compiled using publicly accessible records of players placed on injured lists from 2015 to 2020. These records came from four open access websites: rotoworld.com, fangraphs.com, foxsports.com, and spotrac.com. All injuries were confirmed using the transaction database found on the official MLB website (mlb.com). Results: A greater proportion of pitchers were injured during the first 30 days of the 2020 season compared to the first 30 days of any of the 5 prior seasons (29.74% vs. 11.72%, n=2190, p<0.001) There was a demonstrated increase in injury risk in 2020 for the following anatomic locations: Back and Trunk, Shoulder, Upper Arm and Elbow, Forearm and Wrist, Hand and Finger (p=0.02; CI [0.497-5.783]). When dividing the first month of play in 2020 into equal halves (15 days each), the number of RP injuries increased with time (60% vs 78% p=0.04). Lastly, there was no proportional difference in placement on the short-term vs. long-term IL. Conclusion: A significantly large increase in soft tissue injuries in 2020 compared to the prior five seasons predominantly affected the trunk and the upper extremity of pitchers in the first 30 days of play. Alterations to preseason training and regular season play in the 2020 MLB season due to COVID-19 may have been particularly disadvantageous to professional pitchers who are, at baseline, the most injury prone position.